2014
DOI: 10.1007/s11427-014-4643-0
|View full text |Cite
|
Sign up to set email alerts
|

The herbal compound geniposide rescues formaldehyde-induced apoptosis in N2a neuroblastoma cells

Abstract: The herbal medicine Tong Luo Jiu Nao (TLJN) contains geniposide (GP) and ginsenoside Rg1 at a molar ratio of 10:1. Rg1 is the major component of another herbal medicine, panax notoginseng saponin (PNS). TLJN has been shown to strengthen brain function in humans, and in animals it improves learning and memory. We have previously shown that TLJN reduces amyloidogenic processing in Alzheimer's disease (AD) mouse models. Together this suggests TLJN may be a potential treatment for patients with dementia. Because c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Animal experiments have shown that the abnormal accumulation of formaldehyde promotes Aβ deposition, a main characteristic of AD [52][53][54] in addition to the neurofibrillary tangles [27,55,56] , and induces memory decline and cognitive impairment [12,26] . Therefore, elevation of endogenous formaldehyde may be one of the important risk factors for sporadic AD during aging [57] .…”
Section: Uric Formaldehyde Inversely Correlated With General Cognitivmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments have shown that the abnormal accumulation of formaldehyde promotes Aβ deposition, a main characteristic of AD [52][53][54] in addition to the neurofibrillary tangles [27,55,56] , and induces memory decline and cognitive impairment [12,26] . Therefore, elevation of endogenous formaldehyde may be one of the important risk factors for sporadic AD during aging [57] .…”
Section: Uric Formaldehyde Inversely Correlated With General Cognitivmentioning
confidence: 99%
“…shown that the human body generates and degrades endogenous formaldehyde [6] , and excessive endogenous formaldehyde leads to neurodegenerative diseases [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…甲 醛 参 与 DNA 、 RNA、 组蛋白等甲基化 [27] . 因此, 甲醛代谢失调, 可以 通过影响表观遗传学, 以及蛋白质的异常修饰和分子 聚集, 从而造成包括学习记忆在内的认知损伤 [28,29] .…”
Section: 代谢性疾病的角度来审视Ad 糖、脂或核酸代谢的 图 1 (网络版彩色)阿尔茨海默症的研究和预防窗口前移到临床前unclassified
“…PNS is the main bioactive ingredient of Panax notoginseng, which is considered as activating blood circulation to dissipate stasis [4,5]. In vivo, the combination improved spatial learning and memory and recued amyloid plaques in several AD-like animal models [1,6,7,8]; in vitro, GP and PNS showed to protect neuronal damage caused by formaldehyde [9,10] and promoted the neurite outgrowth of rat hippocampal neurons under oxygen/glucose-deprivation conditions [11]. These data suggest that GP and PNS combination undergoes a potential role of neuroprotection in AD.…”
Section: Introductionmentioning
confidence: 99%